دراسة بنيوية تكوينية في رواية "عرس الزين للطيب صالح - سعيدي, رفيقة; لبيهي, حكيمة; معلول, حكيمة (My University, 2023)
الملخص: .  يقوم المنهج البنيوي التكويني على مجموعة من الضوابط والمنطلقات الأساسية التي صاغها لوسيان غولدمان في شكل مقولات، وهي امتداد للاتجاه الفكري والنقدي الماركسي، فتقوم هذه الدراسة على توضيح مفهوم البنيوية التكوينية ونشأتها، والحديث عن أهم مرتكزات المنهج البنيوي التي اعتمدها لوسيان غولدمان ،وكان تطبيق هذا المنهج على رواية (عرس الزين ) من تأليف الروائي "الطيب صالح " وهي من الروايات العربية المعاصرة ،حيث تتحدث عن واقع المجتمع السوداني، صور فيها الكاتب حياة القرية التي يعيشها السودانيون وجسد فيها الكاتب شخصيات تحمل التناقض في ذاتها ومع غيرها ،إذ تعد شخصية الزين المحورية أبرز مثال على ذلك ،حيث جمع فيها كل الصفات الخارجية القبيحة ونقيضها تضمّن شخصيته الداخلية التي جمعت صفات الطيبة والكرم ،فكانت دراسة تحليلية تهدف إلى التحليل والتفسير لإبراز رؤية يراها الراوي من خلال هذا العمل الأدبي المميز ،والذي من خلاله يعكس واقع المجتمع السوداني ،كما تضمنت هذه الدراسة تطرقا لأهم دلالات البنى الخطابية من خلال الشخصيات والمكان والحوار و السرد والوصف ضمن دراسة بنيوية تكوينية حسب ما أسس لها رائدها الأول" لوسيان غولدمان" من أجل تحليل بنياتها الداخلية والخارجية. Résumé : أو انجلزية The structural-formative approach is based on a set of controls and basic perspectives formulated by "Lucien Goldman" in the form of quotes, which are an extension of the Marxist intellectual and critical approach, This study is based on clarifying the concept of formative structuralism and its origin, and talking about the most important pillars of the structuralist approach adopted by "Lucien Goldman", And it was the application of this approach to the novel (The Wedding of Zein) written by the novelist "Tayyib Salih", which is one of the contemporary Arabic novels, where it talks about the reality of Sudanese society, in which the writer depicted the life of the village that the Sudanese live in, and the writer embodied in it characters that carry contradictions in themselves and with others. The central figure of "Zain" is the most prominent example of this, Where he collected in the novel all the ugly external characteristics, and its opposite includes his inner personality, which collected the characteristics of kindness and generosity, so It was an analytical study aimed at analysis and interpretation to highlight the vision seen by the narrator, through this distinguished literary work, through which it reflects the reality of Sudanese society. This study also touched on the most important semantics of discursive structures through characters, place, dialogue, narration, and description Within a structural study formative, according to what was founded by its first pioneer, "Lucien Goldman", in order to analyze its internal and external structures
Keywords: عربيّــة: بنوية / روية/ عرس الزين; فرنسيــة : Solar Energy - Solar Tracking - Panels